Perivascular Invasion: A Promising Prognostic Parameter for Breast Cancer - Begüm Çalım GÜRBÜZ; Tuçe Söylemez AKKURT; Handan EREN; Hazal İzol ÖZMEN; Ebru ŞEN; Burçin PEHLİVANOĞLU (Medeniyet Medical Journal)
Objective: Angiotropism/perivascular invasion (PVI) is an emerging topic in various types of cancer, with studies primarily focusing on melanoma. However, limited data are available on the significance of PVI in breast cancer. This study aimed to assess the prognostic significance of PVI in breast cancer and its correlation with traditional clinicopathological prognostic parameters. Methods: A total of 150 patients with breast cancer diagnosed between July 2020 and January 2022 were included. Clinicopathological data were retrieved from the hospital records. The presence of PVI was evaluated on hematoxylin&eosin stained slides, and the association between PVI and clinicopathological parameters was statistically analyzed. A p-value of <0.05 was regarded as statistically significant. Results: All patients were female. The mean age was 54.0+-13.6 years (range 26-97 years). PVI was significantly more common in patients with ≥2.5 cm tumors and the absence of PVI showed a significant correlation with a lower histologic grade (p=0.004 and p=0.040, respectively). Lymphovascular invasion (LVI) and perineural invasion (PNI) were also significantly more frequent in tumors with PVI (p=0.001 and 0.02, respectively). There was a statistically significant association between the absence of both PVI and extranodal extension (ENE) (p=0.035). Conclusions: The specific role of PVI in different types of cancer has not yet been clarified. Our findings showed that PVI was significantly associated with tumor size, histological grade, LVI, PNI, and ENE, all of which are well-known negative prognostic factors in breast cancer. The presence of PVI is a promising topic in breast cancer research, and the PVI status in pathology reports may help oncologists perform better risk assessments for patients with breast carcinoma.